Implementasi Augmented Reality pada Latihan Progressive Muscle Relaxation - Afifullah, Fauzi Naufal; Listyorini, Tri; Supriyati, Endang (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2022)
Progressive muscle relaxation therapy is the process of focusing muscle activity to look for tension that occurs in the muscles, this affects the health of our bodies. One possible treatment for high blood pressure is complementary therapy, namely progressive muscle relaxation therapy. Progressive muscle relaxation techniques are deep muscle relaxation techniques that do not require imagination, force or suggestion. However, many people do not know about this. With a technological approach, progressive muscle relaxation therapy is built in an interesting way with augmented reality. The application of augmented reality to progressive muscle therapy is beneficial for the general public, especially those experiencing problems with muscle tension. So that they can do their own therapy according to the directions from the animation